Math, asked by adityabirla39, 7 months ago

Prove the following identity.
♦ Do not spam !!​

Attachments:

Answers

Answered by Anonymous
41

Given

\small\tt\longmapsto{\dfrac{1}{cosecA - cotA} - \dfrac{1}{sinA} = \dfrac{1}{sinA} - \dfrac{1}{cosecA - cotA}}

Formula used

\: \: \: \: \: \: \: \: \: \: \: \: \boxed{\tt{\bigstar{(a + b) (a - b) = a^2 - b^2{\bigstar}}}}

Solution

  • Taking L.H.S

\tt:\implies{L.H.S = \dfrac{1}{cosecA - cotA} - \dfrac{1}{sinA}}

Rationalising

\tiny\tt:\implies{L.H.S = \dfrac{1}{cosecA - cotA} \times \dfrac{cosecA + cotA}{cosecA + cotA} - \dfrac{1}{sinA}}

\small\tt:\implies{L.H.S = \dfrac{cosecA + cotA}{cosec^2A - cot^2A} - cosecA}

\: \: \: \: \: \: \boxed{\orange{cosec^2A - cot^2 = 1}}

\tt:\implies{L.H.S = \cancel{cosecA} + cotA - \cancel{cosecA}}

\tt:\implies{L.H.S = cotA}⠀⠀.....[1]

  • Now, taking R.H.S

\tt:\implies{R.H.S = \dfrac{1}{sinA} - \dfrac{1}{cosecA + cotA}}

Rationalising

\tiny\tt:\implies{R.H.S = \dfrac{1}{sinA} - \dfrac{1}{cosecA + cotA} \times \dfrac{cosecA - cotA}{cosecA - cotA}}

\small\tt:\implies{R.H.S = \dfrac{1}{sinA} - \dfrac{cosecA - cotA}{cosec^2A - cot^2A}}

\: \: \: \: \: \: \boxed{\orange{cosec^2A - cot^2 = 1}}

\tt:\implies{R.H.S = cosecA - (cosecA - cotA)}

\tt:\implies{R.H.S = \cancel{cosecA} - \cancel{cosecA} + cotA}

\tt:\implies{R.H.S = cotA}⠀⠀....[2]

From [1] and [2] we find that

\large{\underline{\sf{\red{L.H.S = R.H.S}}}}

━━━━━━━━━━━━━━━━━━━━━━

Similar questions